2005
DOI: 10.1007/s10531-004-0224-z
|View full text |Cite
|
Sign up to set email alerts
|

An ED-based Protocol for Optimal Sampling of Biodiversity

Abstract: While conservation planning requires good biodiversity data, our knowledge of most living groups is scarce and patchy even in well-sampled regions. Therefore, we need methodologies for rapid assessments for particular groups and regions. Maps of any biodiversity surrogate can be interpolated from even a few well-known sites, but such places are usually lacking. We therefore propose a protocol for designing field surveys to obtain good coverage of pattern variations of biodiversity in a given region. To represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
174
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(180 citation statements)
references
References 70 publications
3
174
0
3
Order By: Relevance
“…3) showed that the number of analyzed root samples was sufficient to detect the majority of fungal types present in the roots as the curve approaches saturation. The estimated-richness curve showed the same tendency as the observed-richness curve, and its slope had a value of 0.018, which was lower than 0.05 (slopes lower than a cutoff value such as 0.05 are complete enough to consider a taxonomic unit or phylotype to be well sampled for studies of biodiversity) (23).…”
Section: Resultsmentioning
confidence: 80%
“…3) showed that the number of analyzed root samples was sufficient to detect the majority of fungal types present in the roots as the curve approaches saturation. The estimated-richness curve showed the same tendency as the observed-richness curve, and its slope had a value of 0.018, which was lower than 0.05 (slopes lower than a cutoff value such as 0.05 are complete enough to consider a taxonomic unit or phylotype to be well sampled for studies of biodiversity) (23).…”
Section: Resultsmentioning
confidence: 80%
“…The Jackknife 1 estimator has been shown to give better results than the other incidence-based estimators, since both seem to be less affected by grain size (Hortal et al 2006). In every grid cell, the number of database records was used as a surrogate of sampling effort (Hortal & Lobo 2005). We use a biodiversity-oriented Geographical information system (DIVA-GIS 7.4, http://www.diva-gis.org/) for the calculation of Jackknife1 estimator of species numbers per grid cell.…”
Section: Methodsmentioning
confidence: 99%
“…We merged the data from three of the 255 grid cells used by them, which had less than 15% of land surface, with their adjacent UTM50. Lobo & Martín-Piera (2002) used species accumulation curves to relate the sampling effort carried out on each cell and the number of species discovered (see also Hortal & Lobo 2005), identifying 82 UTM50 as being well-sampled (Lobo & Martín-Piera 2002). They later excluded seven of these cells, because they either pertained to the Balearic Islands or were identified as outliers due to oversampling (around Madrid and Barcelona).…”
Section: Origin and Geographic Coverage Of Datamentioning
confidence: 99%
“…We assessed the coverage of the environmental and geographical variability of the Iberian Peninsula provided by the well-sampled UTM50 by means of their ED coverage (that is, coverage of the overall Environmental Diversity; see Hortal & Lobo 2005 and references therein). Here, the overall coverage of the environmental and/or spatial variability of a territory provided by a selected subset of areas is calculated as the sum of all the distances from each non-selected area to the selected subset; the lower such sum of distances, the larger is the coverage of the regional variability, in a typically decreasing curve.…”
Section: Origin and Geographic Coverage Of Datamentioning
confidence: 99%